Evaluasi Rekam Medis Elektronik di Tempat Pendaftaran Pasien Gawat Darurat dan Rawat Inap RSUD K.R.M.T Wongsonegoro Kota Semarang - Eka Cintiya Febrianti; Ida Nurmawati; Indah Muflihatin (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
Each hospital is required to hold records or records of all services provided to patients called medical records. Increasing the effectiveness of recording medical data that is accurate, fast, can take advantage of current technological advances through the implementation of the Electronic Medical Record (EMR) system in hospitals. RSUD K.R.M.T Wongsonegoro is one of the hospitals that has implemented an electronic medical record (EMR) especially in the inpatient and emergency department registration units. The application of this electronic medical record still has some flaws that must be evaluated. This study aims to evaluate the implementation of electronic medical records at the emergency and inpatient registrations of Wongsonegoro Hospital. Data collection in this study consisted of observations and interviews. Identification of problems using the TAM (Technology Acceptance Model) method by reviewing from 3 aspects namely perceived usefulness, perceived ease of use, and behavioral intention to use. This type of research is descriptive qualitative by narrating the results of research based on the data obtained. The results obtained from this study are based on the aspect of usefulness (perceived usefulness), namely the use of electronic medical records in TPPGD and TPPRI, making the registration officer work faster and more effective.The aspect of ease (perceived ease of use) obtained from the interview results is that it is able to make it easier to accelerate the registration process in the TPPGD and TPPRI. The behavioral intention to use obtained is that the users of this system really need this electronic medical record and the registration officer at TPPGD and TPPRI plans to use the EMR in the future.